Pemahaman Siswa Kelas IV SD dalam Memahami Konsep Pecahan Berdasarkan Angket - Aisyah Fitriani; Lina Permai Sahra; Suci Puteri Maulia; Muhammad Fendrik; Cici Oktaviani (Lembag, 2025)
This study aimed to analyze the level of understanding of fraction concepts among fourth-grade students at SDIT Al Hidayah Pekanbaru and to identify effective learning strategies. Mathematics, particularly the concept of fractions, often poses a significant challenge at the primary education level. The research employed a descriptive quantitative approach, with primary data collected through the distribution of a questionnaire to 30 students. This questionnaire was designed to measure the students' mastery level of basic concepts, operations, and application of fractions.The findings indicate that the students' level of understanding of fraction concepts is in the very good category. This is evidenced by the questionnaire data, where 63.33% of respondents selected the